Redundancy Payments, Incomplete Labor Contracts, Unemployment and Welfare - Pierre Cahuc; André Zylberberg (Institute for the Study of Labor (IZA), 1999)
It is frequently argued that pure government-mandated severance transfers by the employer to the worker have neither employment nor welfare effect because they can be offset by private transfers from the worker to the employer. In this paper, using a dynamic search and matching model a la Mortensen and Pissarides (1994), we show that it may be not any more the case if labor contracts are incomplete and can be renegotiated by mutual agreement only. Indeed, we show that increases in high severance payments are likely to decrease unemployment but systematically decrease welfare and raise inequality. Moreover, it can be understood that insiders try to get high severance payments through political channels, although they do not fight for such a type of advantage at the firm level.
Keywords: J41; H29; J64; J38; J23; 330; Unemployment; job protection; severance payments; renegotiation; Abfindung; Sozialplan; Theorie der Arbeitslosigkeit; Arbeitsuche; Arbeitsvertrag; Unvollständiger Vertrag; Verhandlungstheorie; Arbeitsmarkttheorie; Wohlfahrtseffekt; Theorie